Women’s Studies, Community Service-Learning, and the Dynamics of Privilege - Muzak, Joanne (Atlantis, 2012)
Drawing on the author’s experiences of incorporating service-learning into Introduction to Women’s Studies courses, this article demonstrates that community service-learning provides a critical opportunity to interrogate the privileges built into postsecondary education. The article asks, what do students understand as "privilege" and what do they come to understand about their positionality via service-learning?